Relationships Between Self-Regulated Learning, Deliberate Practice and the Consideration of Future Consequences for Developing Sport Experts - Bartulovic, Dora (Université d'Ottawa / University of Ottawa, 2016)
This thesis explored relationships (1) between composite and constituent processes of self-regulated learning (SRL) and three sport performance groups, (2) between SRL and different practice variables, and (3) whether these associations depended on an athlete’s consideration of future consequences (CFC). Athletes (N = 272; 200 males; 18-35 yrs; M practice = 13.55 hours/week) completed survey measures for SRL, weekly training including deliberate practice (DP), performance level and CFC. Higher scores in composite SRL were associated with a greater chance of belonging to an elite group, compared to a less-elite and a recreationally competitive group. Self-monitoring predicted greater likelihood of membership in less-elite and elite groups compared to the recreationally competitive group. Self-monitoring predicted greater engagement in total DP hours, and DP in supervised and unsupervised settings. Effort, self-efficacy, and planning were notable in some results, but contributions were less significant. CFC had no moderating effect, however it was correlated with SRL.
Keywords: self-regulated learning; expertise; SRL-SRS; self-monitoring; deliberate practice; CFC